The relationship between vitamin D status and disease activity in Iraqi systemic lupus erythematosus patients - Zamin Abdulhusssein Al-Sarray; Raghad Hassan Hussein; Ali Hussein Al-Hafidh; Izzat Abdulsatar Al-Rayahi (Journal of the Pakistan Medical Association, 2024)
Objective: To find the relationship between vitamin D deficiency and the activity of systemic lupus erythematosusin Iraqi patients. Method: The case-control study was conducted at Baghdad Teaching Hospital, Baghdad, Iraq, from July to October2018, and comprised systemic lupus erythematosus patients regardless of age and gender visiting theRheumatology outpatient clinic. Serum levels of complement protein 3, complement protein 4, anti-doublestrandeddeoxyribonucleic acid and 25-hydroxy vitamin D were estimated. Based on disease activity scores, patientswere divided into moderate activity group SLE-M and severe activity group SLE-S. Healthy subjects matched for ageand gender were also enrolled as the control group. Data was analysed using Graph Pad Prism 5.0. Results: Of the 150 subjects, 62(41.3%) were in SLE-S group, 38(25.3%) in SLE-M and 59(33.3%) in the control group.Among the patients, 97(97%) were females and 3(3%) were males, with a female-to-male ratio of 32:1. The patients’age range was <10 - Greater than or equal to 50 years, while the control group consisted of 2 (4%) males and 48 (96%) females with an agerange of <10- Greater than or equal to 50. The mean levels of serum complement protein 3, complement protein 4 and vitamin D levelswere significantly lower in the patient groups compared to the controls (p<0.05). Conclusion: Systemic lupus erythematosus patients suffered from either vitamin D deficiency or insufficiency, andlow vitamin D levels were found related to disease activity. Key Words: Rheumatology, Vitamin D, Lupus Erythematosus, Systemic, DNA, Proteins, Ambulatory Care